The sizes of maximal \((v,k,k-2,k-1)\) optical orthogonal codes


An optical orthogonal code (OOC) is a family of binary sequences having good auto- and cross-correlation properties. Let \(\Phi (v,k,\lambda _{a},\lambda _{c})\) denote the largest possible size among all \((v,k,\lambda _{a},\lambda _{c})\)-OOCs. A \((v,k,\lambda _{a},\lambda _{c})\)-OOC with \(\Phi (v,k,\lambda _{a},\lambda _{c})\) codewords is said to be maximal. In this paper, we research into maximal \((v,k,k-2,k-1)\)-OOCs and determine the exact value of \(\Phi (v,k,k-2,k-1)\). This generalizes the result on the special case of \(k=4\) by Huang and Chang in 2012. Distributions of differences with maximum multiplicity are analyzed by several classes to deal with the general case for all possible v and k.

This is a preview of subscription content, log in to check access.

Access options

Buy single article

Instant unlimited access to the full article PDF.

US$ 39.95

Price includes VAT for USA

Subscribe to journal

Immediate online access to all issues from 2019. Subscription will auto renew annually.

US$ 199

This is the net price. Taxes to be calculated in checkout.


  1. 1.

    Abel R.J.R., Buratti M.: Some progress on \((v,4,1)\) difference families and optical orthogonal codes. J. Combin. Theory Ser. A 106, 59–75 (2004).

  2. 2.

    Alderson T.L., Mellinger K.E.: Families of optimal OOCs with \(\lambda =2\). IEEE Trans. Inform. Theory 54, 3722–3724 (2008).

  3. 3.

    Brickell E.F., Wei V.K.: Optical orthogonal codes and cyclic block designs. Congr. Numer. 58, 175–192 (1987).

  4. 4.

    Buratti M.: A powerful method for constructing difference families and optimal optical orthogonal codes. Des. Codes. Cryptogr. 5, 13–25 (1995).

  5. 5.

    Buratti M., Momihara K., Pasotti A.: New results on optimal \((v,4,2,1)\) optical orthogonal codes. Des. Codes Cryptogr. 58, 89–109 (2011).

  6. 6.

    Buratti M., Pasotti A., Wu D.: On optimal \((v,5,2,1)\) optical orthogonal codes. Des. Codes. Cryptogr. 68, 349–371 (2013).

  7. 7.

    Chang Y., Ji L.: Optimal \((4up, 5, 1)\) optical orthogonal codes. J. Combin. Des. 12, 346–361 (2004).

  8. 8.

    Chang Y., Miao Y.: Constructions for optimal optical orthogonal codes. Discret. Math. 261, 127–139 (2003).

  9. 9.

    Chang Y., Fuji-Hara R., Miao Y.: Combinatorial constructions of optimal optical orthogonal codes with weight \(4\). IEEE Trans. Inform. Theory 49, 1283–1292 (2003).

  10. 10.

    Chung H., Kumar P.V.: Optical orthogonal codes-New bounds and an optimal construction. IEEE Trans. Inform. Theory 36, 866–873 (1990).

  11. 11.

    Chung F.R.K., Salehi J.A., Wei V.K.: Optical orthogonal codes: design, analysis, and applications. IEEE Trans. Inform. Theory 35, 595–604 (1989).

  12. 12.

    Huang Y., Chang Y.: The sizes of optimal \((n,4,\lambda,3)\) optical orthogonal codes. Discret. Math. 312, 3128–3139 (2012).

  13. 13.

    Huang Y., Chang Y.: Two classes of optimal two-dimensional OOCs. Des. Codes. Cryptogr. 63, 357–363 (2012).

  14. 14.

    Kwong W.C., Perrier P.A., Prucnal P.R.: Performance comparison of asynchronous and synchronous code-division multiple-access techniques for fiber-optical local area networks. IEEE Trans. Commun. 39, 1625–1634 (1991).

  15. 15.

    Ma S., Chang Y.: A new class of optimal optical orthogonal codes with weight five. IEEE Trans. Inform. Theory 50, 1848–1850 (2004).

  16. 16.

    Maric S.V., Lau K.N.: Multirate fiber-optic CDMA: system design and performance analysis. J. Lightwave Technol. 16, 9–17 (1998).

  17. 17.

    Maric S.V., Moreno O., Corrada C.J.: Multimedia transmission in fiber-optic LANs using optical CDMA. J. Lightwave Technol. 14, 2149–2153 (1996).

  18. 18.

    Momihara K., Buratti M.: Bounds and constructions of optimal \((n,4,2,1)\) optical orthogonal codes. IEEE Trans. Inform. Theory 55, 514–523 (2009).

  19. 19.

    Salehi J.A.: Code division multiple-acess techniques in optical fiber networks-Part I: fundamental principles. IEEE Trans. Commun. 37, 824–833 (1989).

  20. 20.

    Salehi J.A., Brackett C.A.: Code division multiple-acess techniques in optical fiber networks-Part II: Systems performance analysis. IEEE Trans. Commun. 37, 834–842 (1989).

  21. 21.

    Wang X., Chang Y.: Further results on optimal \((v,4,2,1)\)-OOCs. Discret. Math. 312, 331–340 (2012).

  22. 22.

    Yang Y.: New enumeration results about the optical orthogonal codes. Inform. Process. Lett. 40, 85–87 (1991).

  23. 23.

    Yin J.: Some combinatorial constructions for optical orthogonal codes. Discret. Math. 185, 201–219 (1998).

Download references


The authors would like to thank Prof. Yanxun Chang for many valuable suggestions and comments. They also wish to thank Prof. Marco Buratti and two anonymous referees for carefully reading the manuscript and suggesting several corrections and improvements.

Author information

Correspondence to Junling Zhou.

Additional information

Publisher's Note

Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Supported by NSFC Grants 11571034 and 11971053.

Communicated by M. Buratti.



Proof of Lemma 2.1

Denote \(A=\{x_{0},x_{1},\ldots ,x_{m-1}\}\) where \(x_{i}=i\tau \) for \(0\le i\le m-1\). List the differences of \(\Delta A\) in the following \(m\times m\) matrix M:

$$\begin{aligned} M=\begin{pmatrix} *&{}\quad \tau &{}\quad 2\tau &{}\quad \cdots &{}\quad (m-2)\tau &{}\quad (m-1)\tau \\ -\tau &{}\quad *&{}\quad \tau &{}\quad \cdots &{}\quad (m-3)\tau &{}\quad (m-2)\tau \\ -2\tau &{}\quad -\tau &{}\quad *&{}\quad \cdots &{}\quad (m-4)\tau &{}\quad (m-3)\tau \\ \vdots &{}\quad \vdots &{}\quad \vdots &{}\quad \ddots &{}\quad \vdots &{}\quad \vdots \\ -(m-2)\tau &{}\quad -(m-3)\tau &{}\quad -(m-4)\tau &{}\quad \cdots &{}\quad *&{}\quad \tau \\ -(m-1)\tau &{}\quad -(m-2)\tau &{}\quad -(m-3)\tau &{}\quad \cdots &{}\quad -\tau &{}\quad *\end{pmatrix}, \end{aligned}$$

where the (ij)-entry denotes the difference \(x_{j}-x_{i}\) (\(i\ne j\)).

Clearly, when \({{\text {ord}}}(\tau )=m\) (so A forms a subgroup of \({\mathbb {Z}}_v\)), we have \(-i\tau \equiv (m-i)\tau ~(\bmod ~v)\) and thus \(\Delta A=[(i\tau )^{m}:1\le i\le m-1].\) When \({{\text {ord}}}(\tau )=m+1\), we have \(-i\tau \equiv (m+1-i)\tau ~(\bmod ~v)\). Hence it is not difficult to have that \( \Delta A=[(i\tau )^{m-1}:1\le i\le m].\)

Let \({{\text {ord}}}(\tau )=d\ge m+2\). It is obvious that \(\tau \not \equiv -i\tau \)\((\bmod ~v)\) for all \(1\le i\le m-1\) and thus \(\lambda _{\Delta X}(\pm \tau )=m-1\). Besides, for \(2\le i\le m-1\), we have \(i\tau \equiv -(d-i)\tau \)\((\bmod ~v)\) occurring in M at most \((m-i)+(i-2)=m-2\) times. Hence, \(\lambda _{\Delta A}(\pm \tau )=m-1\) and \(\lambda _{\Delta A}(\sigma )\le m-2\) for \(\sigma \ne \pm \tau \). This completes the proof. \(\square \)

Proof of Lemma 2.2

Obviously we have

$$\begin{aligned} \Delta Y=(\bigcup _{0\le i\le \frac{h}{d}-1}\Delta Y_{i})\bigcup (\bigcup _{\begin{array}{c} 0\le i,j\le \frac{h}{d}-1\\ i\ne j \end{array}}\Delta (Y_{i},Y_{j}))=D\cup D'. \end{aligned}$$

Since \(Y_{i}=y_{i}+\left\langle \tau \right\rangle \) for \(0\le i\le \frac{h}{d}-1\), we have \(\Delta Y_{i}=\Delta (\left\langle \tau \right\rangle )=[(i\tau )^{d}:1\le i\le d-1]\) by Lemma 2.1. Hence, \(D=\bigcup _{0\le i\le \frac{h}{d}-1}\Delta Y_{i}=[(i\tau )^{h}:1\le i\le d-1]\), proving part (ii). It follows that every nonzero element of \(\left\langle \tau \right\rangle \) is a difference of multiplicity h in D and thus also in \(\Delta Y\) as \(|Y|=h\). Consequently, \(D\cap D'=\emptyset \), proving part (i).

Next we show that, for any \( 0\le i,j\le \frac{h}{d}-1\) with \(i\ne j\),

$$\begin{aligned} \lambda _{\Delta (Y_{i},Y_{j})}(\delta )=d\ \mathrm{for\ every\ } \delta \in \Delta (Y_{i},Y_{j}). \end{aligned}$$

Because \(\delta \in \Delta (Y_{i},Y_{j}),\) assume that \(\delta =(y_{j}+a\tau )-(y_{i}+b\tau )=y_j-y_i+\alpha \) where \(\alpha =a\tau -b\tau \in \Delta (\left\langle \tau \right\rangle )\cup \{0\}\). Applying Lemma 2.1 yields \(\lambda _{\Delta (\left\langle \tau \right\rangle )}(\alpha )=d\) if \(\alpha \ne 0\). Clearly \(0=i\tau -i\tau \) for all \(0\le i\le d-1\). Thus (6) holds.

Let \(0\le i\le \frac{h}{d}-1\) and i be fixed. Then we have

$$\begin{aligned} \Delta (Y_{i},Y_{j})\cap \Delta (Y_{i},Y_{l})=\emptyset ,\ 0\le j,l\le \frac{h}{d}-1,i\ne j\ne l \ne i. \end{aligned}$$

Otherwise, we have \(y_{j}-y_{i}+\alpha = y _{l}-y_{i}+\beta \) for some \(\alpha ,\beta \in \left\langle \tau \right\rangle =\left\langle {v\over d}\right\rangle \) so that \(y_{j}=y_{l}+\beta -\alpha \), which contradicts with that \(y_j\ne y_l\) and \(y_{j},y_{l}\in {\mathbb {Z}}_{\frac{v}{d}}\).

Let \(\delta \in D'\) be fixed. By (7), given \(0\le i\le {h\over d}-1\), if \(\delta \in \bigcup _{i\ne j}\Delta (Y_i,Y_j)\), then there exists at most one j with \(0\le j\le {h\over d}-1\) such that \(\delta \in \Delta (Y_{i},Y_{j})\). Hence, we have \(|I|\le \frac{h}{d}\), i.e., \(|I|=\frac{h}{d}-a\) for some integer a with \(0\le a\le {h\over d}-1\), where

$$\begin{aligned} I=\{(i,j):\delta \in \Delta (Y_{{i}},Y_{j}),0\le i,j\le \frac{h}{d}-1,i\ne j\}. \end{aligned}$$

Then combining with (6) and using part (i), we have that \(\lambda _{\Delta Y}(\delta )=\lambda _{D'}(\delta )=|I|\cdot d=h-ad\), proving (iii). \(\square \)

Proof of Lemma 2.3

  1. (i)

    Let \({{\text {O}}}(X)\in \Lambda (k-1).\) Suppose that \(\lambda _{\Delta X}(\tau )=\lambda (\Delta X)=k-1\). Then clearly we have \(\tau \ne 0\) and \(|X\cap (X+\tau )|=k-1\). Obviously \(|X\cap (X+(v-\tau ))|=k-1\) if and only if \(|X\cap (X+\tau )|=k-1\). Thus there is \(\tau \) with \(1\le \tau \le \lfloor {v\over 2}\rfloor \) such that \(|X\cap (X+\tau )|=k-1\). This proves that \(\Lambda (k-1)\) is contained in the right-hand side set. Conversely, let \(X\in \Omega (v,k)\) satisfy \(|X\cap (X+\tau )|=k-1\) for some \(1\le \tau \le \lfloor {v\over 2}\rfloor \). Then \(\lambda _{\Delta X}(\tau )= k-1\). We need to show that \(\lambda (\Delta X)=k-1\) (meaning X belongs to a full orbit) and then \({{\text {O}}}(X)\in \Lambda (k-1).\) Obviously \(\lambda (\Delta X)\ge \lambda _{\Delta X}(\tau )= k-1\). If \(\lambda (\Delta X)=k\), then there exists \(\sigma \in {\mathbb {Z}}_{v}^*\) such that \(X=X+\sigma \). Denote \({{\text {ord}}}(\sigma )=d\). By Corollary 1.4, we have \(X=X_0+\left\langle \sigma \right\rangle \) for some \(X_0\in \Omega (\frac{v}{d},\frac{k}{d}).\) Note that \(d\ge 2\) as \(\sigma \ne 0\). By Lemma 2.2, \(\lambda _{\Delta X}(\tau )=k\) or \(\lambda _{\Delta X}(\tau )\le k-d\le k-2\), contradicting to \(\lambda _{\Delta X}(\tau )=k-1\). This proves (i).

  2. (ii)

    This follows immediately by noting that we have shown any \(X\in \Gamma (k-1)\) belongs to a full orbit. \(\square \)

Proof of Lemma 3.1

Write X as

$$\begin{aligned} X=Y\cup Z=(Y'+\left\langle \tau \right\rangle )\cup \{x,x+\tau ,\ldots ,x+(m-1)\tau \}, \end{aligned}$$

where \(Y=Y+\tau \) can be written as \(Y=Y'+\left\langle \tau \right\rangle \) for some \(Y'=\{y_{0},y_{1},\ldots ,y_{\frac{k-m}{d}-1}\}\in \Omega ({v\over d},{k-m\over d})\) by applying Corollary 1.4. For convenience, denote \(y_{\frac{k-m}{d}}=x\), \(Y_{\frac{k-m}{d}}=Z\), and \(Y_{i}=\{y_{i}\}+\left\langle \tau \right\rangle \) for \(0\le i\le \frac{k-m}{d}-1\). Then \(X=\bigcup _{i=0}^{\frac{k-m}{d}}Y_{i}\) and \(\Delta X=D\cup D'\), where

$$\begin{aligned} D=\bigcup _{0\le i\le \frac{k-m}{d}}\Delta Y_{i},\ D'=\bigcup _{\begin{array}{c} 0\le i,j\le \frac{k-m}{d}\\ i\ne j \end{array}}\Delta (Y_{i},Y_{j}). \end{aligned}$$

By Lemma 2.2, we have \(D=[(i\tau )^{k-m}:1\le i\le d-1]\cup \Delta Z\). So it is clear that all differences of D belong to \(\left\langle \tau \right\rangle \), giving that if \(\delta \in \Delta X\) and \(\delta \notin \left\langle \tau \right\rangle \) then \(\delta \in D'\).

Let \(\delta \in \Delta (Y_{i},Y_{j})\) where \(0\le i,j\le \frac{k-m}{d}\) and \(i\ne j\). Then we have

$$\begin{aligned} \lambda _{\Delta (Y_{i},Y_{j})}(\delta )=\left\{ \begin{array}{ll} d, &{}0\le i,j\le \frac{k-m}{d}-1,i\ne j, \\ m, &{}\frac{k-m}{d}\in \{i,j\},i\ne j.\end{array}\right. \end{aligned}$$

Equation (8) holds for \(0\le i,j\le \frac{k-m}{d}-1\) and \(i\ne j\) by similar analysis to the proof of (6) in Lemma 2.2. Now we prove the case that \(i=\frac{k-m}{d}\) or \(j=\frac{k-m}{d}\) with \(i\ne j\). W.l.o.g. let \(i=\frac{k-m}{d}\) and \(i\ne j\). Since \(\alpha \in \Delta (Y_{\frac{k-m}{d}},Y_{j})\), we may write \(\alpha =y_{j}-y_{\frac{k-m}{d}}+\beta \) for some \(\beta \in \Delta (Z_{0},\left\langle \tau \right\rangle )\) with \(Z_{0}=\{0,\tau ,\ldots ,(m-1)\tau \}.\) It is not difficult to learn that \(\Delta (Z_{0},\left\langle \tau \right\rangle ) =[(i\tau )^m:0\le i\le d-1]\) by noting that \(i\tau =(l+i)\tau -l\tau \) for all \(0\le l\le m-1\). Hence \(\lambda _{\Delta (Y_{\frac{k-m}{d}},Y_{j})}(\alpha )=\lambda _{\Delta (Z_{0},\left\langle \tau \right\rangle )}(\beta )=m\).

Let \(0\le i\le \frac{k-m}{d}\) be fixed. By the same argument for (7) in the proof of Lemma 2.2, we have

$$\begin{aligned}&\Delta (Y_{i},Y_{j})\cap \Delta (Y_{i},Y_{l})=\emptyset ,\ \Delta (Y_{j},Y_{i})\cap \Delta (Y_{l},Y_{i})=\emptyset ,\nonumber \\ {}&\quad 0\le j,l\le \frac{k-m}{d}-1,i\ne j\ne l \ne i. \end{aligned}$$

Let \(\delta \in D'\) be fixed. By (9), given \(0\le i\le {k-m\over d}\), if \(\delta \in \bigcup _{j\notin \{i, {k-m\over d}\}}\Delta (Y_i,Y_j)\), then there exists at most one j with \(0\le j\le {k-m\over d}-1\) such that \(\delta \in \Delta (Y_{i},Y_{j})\). Similarly, there exists at most one i with \(0\le i\le {k-m\over d}-1\) such that \(\delta \in \Delta (Y_{i},Y_{k-m\over d})\). Hence, we have \(|I|\le \frac{k-m}{d}+1\) and \(|I'|\le 1,\) where

$$\begin{aligned}&I=\{(i,j):\delta \in \Delta (Y_{{i}},Y_{j}),0\le i\le \frac{k-m}{d},0\le j\le \frac{k-m}{d}-1,i\ne j\},\\&I'=\{i:\delta \in \Delta (Y_{i},Y_{\frac{k-m}{d}}),0\le i\le \frac{k-m}{d}-1\}. \end{aligned}$$

Combining with (8) yields that

$$\begin{aligned} \lambda _{D}(\delta )=\left\{ \begin{array}{ll} (|I|-1)d+(|I'|+1)m, &{}\mathrm{if\ }(\frac{k-m}{d},j)\in I\ \mathrm{for\ some\ } j, \\ |I|d+|I{'}|m, &{}\mathrm{otherwise}.\end{array}\right. \end{aligned}$$

Now we prove the conclusion by contradiction. Note that if \(m=1\) then \(Z=\{x\}\) is independent of \(\tau \). So w.l.o.g. we let \(G_Y=\left\langle \tau \right\rangle \) when \(m=1\). Assume that \(\lambda _{\Delta X}(\sigma )=k-1\) and \(\sigma \notin \left\langle \tau \right\rangle \). Then \(\sigma \in D'\) by previous arguments. We consider the following cases.

  1. (a)

    \((\frac{k-m}{d},j)\in I\) and \(|I'|=0\). Then \(\lambda _{\Delta X}(\sigma )=(|I|-1)d+m\). Because \(|I|\le \frac{k-m}{d}+1\) and \(\lambda _{\Delta X}(\sigma )=k-1\), we must have \(k-1=\lambda _{\Delta X}(\sigma )=k-ad\) for some positive integer a, which contradicts to \(d\ge m+2\ge 3\).

  2. (b)

    \((\frac{k-m}{d},j)\in I\) and \(|I'|=1\). In such a case we have \(\lambda _{\Delta X}(\sigma )=(|I|-1)d+2m=k-ad+m\) for some nonnegative integer a, contradicting to \(\lambda _{\Delta X}(\sigma )=k-1\) because \(d\ge m+2\).

  3. (c)

    \((\frac{k-m}{d},j)\not \in I\) and \(|I'|=1\). Then \(\lambda _{\Delta X}(\sigma )=|I|d+m\) and \(|I|\le \frac{k-m}{d}\). Similarly to (a), we have a contradiction \(k-1=k-ad\) (\(a\ge 1\)).

  4. (d)

    \((\frac{k-m}{d},j)\not \in I\) and \(|I'|=0\). Then \(\lambda _{\Delta X}(\sigma )\le {k-m\over d}\cdot d= k-m.\) Since \(\lambda _{\Delta X}(\sigma )= k-1,\) we have \(m=1\). Thus \(X=Y\cup \{x\}\) and \(Y=Y+\tau \). It is easy to show \(\Delta X=\Delta Y\cup \Delta (\{x\},Y)\cup \Delta (Y,\{x\})\). By Lemma 2.2, \(\lambda _{\Delta Y}(\sigma )=k-1-ad\) for some nonnegative integer a. Hence \(\lambda _{\Delta Y}(\sigma )=k-1\) or \(\lambda _{\Delta Y}(\sigma )\le k-4\) as \(d\ge 3\). Clearly \(\lambda (\Delta (Y,\{x\}))=\lambda (\Delta (\{x\},Y)) =1\). From \(\lambda _{\Delta X}(\sigma )= k-1,\) we must have \(\lambda _{\Delta Y}(\sigma )= k-1\), yielding \(\sigma \in G_Y=\left\langle \tau \right\rangle \), a contradiction.

This completes the proof. \(\square \)

Proof of Lemma 3.2

The existence of \(\hat{X}\) and x is obvious if \(X\in \Gamma _{1,1}\) because \(d=k+1\). So we let \(X\in \Gamma _{2,2}\) be of Type II with respect to \((Y,Z,\tau ,d,m,z)\) where \(d=m+1\). Then \(X=Y\cup Z\) where \(Y=Y+\tau \), \(Z=\{z,z+\tau ,\ldots ,z+(m-1)\tau \}\), and \({{\text {ord}}}(\tau )=d=m+1\). Clearly \(Z=(z+\left\langle \tau \right\rangle )\setminus \{z+m\tau \}\). By applying Corollary 1.4, we have \(Y=Y_0+\left\langle \tau \right\rangle \) for some \(Y_0=\{y_{0},y_{1},\ldots ,y_{\frac{k-m}{d}-1}\}\in \Omega ({v\over d},{k-m\over d})\). Then letting \(\hat{X}=(Y_0\cup \{z\})+\left\langle \tau \right\rangle \) and \(x=z+m\tau \) yields \(X=\hat{X}\setminus \{x\}\). Obviously \(\left\langle \tau \right\rangle \le G_{\hat{X}}\) and thus \(\hat{X}\) generates a short orbit. This proves the existence of \(\hat{X}\) and x.

In the sequel we suppose that \(X=(Y_0+\left\langle \tau \right\rangle )\cup Z=\hat{X}\setminus \{x\}\) as above and suppose \(\tau \) is a generator of \(G_{\hat{X}}\). Obviously

$$\begin{aligned} \Delta X=\Delta \hat{X}\setminus (\Delta (X,\{x\})\cup \Delta (\{x\},X)). \end{aligned}$$

For convenience, denote \(y_{\frac{k-m}{d}}=z\) and \(Y_{i}=\{y_{i}\}+\left\langle \tau \right\rangle \) for \(0\le i\le \frac{k-m}{d}\). Then \(\hat{X}=\bigcup _{i=0}^{\frac{k-m}{d}}Y_{i}\) and

$$\begin{aligned} \Delta \hat{X}= D\cup D',\ \mathrm{where}\ D=\bigcup _{{ 0\le i\le \frac{k-m}{d}}}\Delta Y_{i},\ D'=\bigcup _{\begin{array}{c} 0\le i,j\le \frac{k-m}{d}\\ i\ne j \end{array}}\Delta (Y_{i},Y_{j}). \end{aligned}$$

By Lemma 2.2, for any \(\delta \in {\mathbb {Z}}_v^*\), we have \(\lambda _{\Delta \hat{X}}(\delta )=k+1\) or \(\lambda _{\Delta \hat{X}}(\delta )\le k+1-d\le k-1\) because \(d\ge 2\). Obviously, \(\lambda (\Delta (X,\{x\}))=\lambda (\Delta (\{x\},X)) =1\). Now suppose that \(\lambda _{\Delta X}(\sigma )=k-1\) for some \(\sigma \in {\mathbb {Z}}_v^*\). Then (i) \(\lambda _{\Delta \hat{X}}(\sigma )=k+1\) and \(\lambda _{\Delta (\{x\},X)}(\sigma )=\lambda _{\Delta (X,\{x\})}(\sigma )=1\), or (ii) \(\lambda _{\Delta \hat{X}}(\sigma )=k-1\), \(d=2\), and \(\lambda _{\Delta (\{x\},X)}(\sigma )=\lambda _{\Delta (X,\{x\})}(\sigma )=0\). Now we show the latter case (ii) is impossible. Otherwise, we have \(d=2\), \(m=1\) and hence \(\hat{X}\) can be written as \(\hat{X}=X_0+\left\langle {v\over 2}\right\rangle \) where \(X_0=\{x_0,x_1,\ldots ,x_{k-1\over 2}\}\in \Omega ({v\over 2},{k+1\over 2})\) and \(x_0\equiv x\) (mod \({v\over 2}\)). From \(\lambda _{\Delta \hat{X}}(\sigma )=k-1\), it follows that \(\lambda _{\Delta X_0}(\sigma _0)={k-1\over 2}\), where \(\sigma _0\equiv \sigma \) (mod \({v\over 2}\)) and \(\sigma _0\in {\mathbb {Z}}_{v\over 2}\). Consider the expression of \(\sigma _0\) as the differences \(x_{k_i}-x_{j_i}\) where \(1\le i\le {k-1\over 2}\) and \(0\le j_i,k_i\le {k-1\over 2}\). It is easy to show that \(x_0\in \{x_{ j_i}:1\le i\le {k-1\over 2}\}\cup \{x_{ k_i}:1\le i\le {k-1\over 2}\}\), meaning \(\lambda _{\Delta (X,\{x\})}(\sigma )=1\) or \(\lambda _{\Delta (\{x\},X)}(\sigma )=1\), a contradiction. To sum up, if \(\lambda _{\Delta X}(\sigma )=k-1\) then \(\lambda _{\Delta \hat{X}}(\sigma )=k+1\). Conversely, if \(\lambda _{\Delta \hat{X}}(\sigma )=k+1\), then \(\sigma \) can be expressed as differences of \(\hat{X}\) in exactly \(k+1\) times, meaning \(\lambda _{\Delta (\{x\},X)}(\sigma )=\lambda _{\Delta (X,\{x\})}(\sigma )=1\) and hence \(\lambda _{\Delta X}(\sigma )=k-1\). As a result, \(\lambda _{\Delta X}(\sigma )=k-1\) if and only if \(\lambda _{\Delta \hat{X}}(\sigma )=k+1\), or equivalently, \(\sigma \in G_{\hat{X}}\). \(\square \)

Rights and permissions

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Fang, Z., Zhou, J. The sizes of maximal \((v,k,k-2,k-1)\) optical orthogonal codes. Des. Codes Cryptogr. (2020) doi:10.1007/s10623-020-00714-1

Download citation


  • List of differences
  • Maximal
  • Optical orthogonal code
  • Orbit
  • Stabilizer

Mathematics Subject Classification

  • 05B30
  • 94B65
  • 94C30